Structural influences on involvement in European homegrown jihadism: a case study - Schuurman, Bart (Terrorism and political violence, 2018)
This article empirically assesses the applicability of structural-level hypotheses for involvement in terrorism within the context of European homegrown jihadism. It uses these hypotheses to study how structural factors influenced involvement in the Dutch “Hofstadgroup.” Structural factors enabled the group’s emergence and its participants’ adoption of extremist views. They also motivated involvement in political violence and a shift in some participants’ focus from joining Islamist insurgents overseas to committing terrorism in the Netherlands. Finally, structural factors precipitated an actual terrorist attack. No support is found for the frequently encountered argument that discrimination and exclusion drive involvement in European homegrown jihadism. Instead, geopolitical grievances were prime drivers of this process.